Specific higher levels of serum uric acid might have a protective effect on bone mineral density within a Chinese population over 60 years old: a cross-sectional study from northeast China - Chen F (Dove Medical Press, 2019)
Feng Chen,1 Yingfang Wang,1 Yan Guo,1 Jiabei Wang,1 Aolin Yang,2 Qingqing Lv,2 Yixuan Liu,1 Guojing Ma,1 Ying Liu,3 Difei Wang11Department of Geriatrics, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning 110001, People’s Republic of China; 2Department of Nutrition, the First Affiliated Hospital of China Medical University, Shenyang, Liaoning 110001, People’s Republic of China; 3Department of Biochemistry and Molecular Biology, China Medical University, Shenyang, Liaoning 110122, People’s Republic of ChinaBackground and objective: Oxidative stress has been demonstrated to be a mechanism that leads to bone mass reduction, and according to many studies, serum uric acid (UA) is a strong endogenous antioxidant that can protect bone mineral density (BMD). To date, there have been no large-scale, cross-sectional studies based on the population in northeast China to assess the relationship between serum UA and BMD. Therefore, we examined the association between serum UA and BMD among a Chinese population older than 60 years old in northeast China.Methods: This research was a cross-sectional study of 3465 Chinese individuals over 60 years old in nine communities from the city of Shenyang, which is the capital of northeast China’s Liaoning Province. Participants were stratified into three groups by serum UA or BMD levels, and then Pearson’s correlation analysis and multiple regression analysis were used to study the relationship between serum UA and BMD.Results: We found that participants with higher serum UA levels had significantly greater BMD and T-values compared to those of participants with lower serum UA levels. After adjusting for confounding factors, Pearson’s correlation analysis and multiple regression analysis showed that higher serum UA levels remained associated with higher BMD levels (P<0.05). In different models, the prevalence of osteoporosis (OP) among participants with higher serum UA levels was reduced by 23% to 26% (P<0.05) compared to that in individuals with lower serum UA levels. In addition, serum UA levels were negatively correlated with estimated glomerular filtration rate (eGFR) and positively correlated with 25-hydroxy vitamin D3 [25-(OH)D3] (P<0.05).Conclusion: We concluded that higher serum UA levels are associated with greater BMD, and serum UA might have a protective effect on bone metabolism due to its antioxidant properties.Keywords: serum uric acid, bone mineral density, osteoporosis